Migration of neotropical fishes in a free flowing river stretch: evaluation of biotelemetry as study method, insights about partial migration, and consequences for conservation - Peressin, Alexandre (2022)
In freshwater migratory fish, it is common that at each breeding season some individuals make the decision to migrate and others remain stationary, a phenomenon known as partial migration. However, the mechanisms and details involved in partial migration are not known in Neotropical fish. Even basic details of the migratory cycle of many species are not known for these fishes. This fact is worrying when observed that migratory fishes are the most relevant for fishing and food, but also the most threatened by dams and overfishing. The deepening of this knowledge requires techniques such as telemetry, which, although it provides data with great precision, is invasive and it effects on Neotropical species behavior are not investigated. Thus, from 60 specimens of Prochilodus lineatus bred in captivity and divided into three treatments (control, surgery without tagging, and tagged fish) it was shown that mortality (25%) and rejection (20%) are significant. However, after recovery, the reproductive capacity of tagged females is similar to untagged ones (Article I). Then, two species of Prochilodus were studied with radiotransmitters and eggs and larvae samples in a natural environment, a stretch of the São Francisco River free of dams that extends for 450 km upstream of the Três Marias reservoir. Twenty-five specimens of P. argenteus were tagged in 2019 at a known feeding site in this stretch (Article II) and 200 specimens of P. costatus were tagged in 2019 and 2020 at their breeding and feeding sites (Article III). In both species, 50% of the fish migrated upstream between late September or early October to December, reaching upstream sites located at/above floodplain. These were also the only places where eggs of the two species were found, showing that spawning is concentrated in individuals present in these upstream stretches, considered vital for the maintenance of the populations studied. The migratory window starts after the first positive changes in river level, showing the close relationship of these species with the natural flow pattern. However, condition and weight factors were not relevant for the decision to migrate in P. costatus. Individuals of this species that migrated in consecutive breeding seasons had the same spawning site as destination, characterizing reproductive homming. There are individuals of P. costatus residing in the breeding site, however, the condition factor and weight of the individuals were higher in the feeding site, showing that these places offer better conditions to the residents. Therefore, it is recommended to focus inspection efforts on spawning sites during the breeding season, in addition to providing natural flow and maintaining free stretches where populations of these species are able to complete their life cycle. Additionally, long-term studies conducted in the northern hemisphere have pointed changes in the migratory pattern of fish in response to climate change. In this sense, it is urgent to annually monitor the migration of Neotropical fish in order to identify possible changes in response to climate change, since migratory species that do not adapt to these changes are highly vulnerable.